GENETIC CORRELATION AND CHARACTER ASSOCIATION OF COMMON BEAN (Phaseolus Vulgaris) IN SUDAN SAVANNA OF NIGERIA - Shaibu, Abdulwahab Saliu; Ossai, A. (FUDMA JOURNAL OF SCIENCES, 2023)
Variation is the foundation of crop breeding and its identification is the key to success or failure of any breeding programme. Knowledge about levels and pattern of genetic diversity can be an invaluable aid in crop breeding for diverse application as well as analysis of genetic variability in cultivars. This research was aimed at assessing the genetic correlation and character association of Phaseolus vulgaris (common bean) in Sudan Savanna of Nigeria. The materials used were five (5) accessions of Phaseolus bean which were laid in a Randomized Complete Block Design and replicated three times. The mean performance of the varieties was determined as well as correlation of the traits measured. The result obtained shows a highly significant genetic diversity among the Phaseolus cultivars studied in terms of morphological traits and agronomic performance. The correlation result also shows more of genetic effects than the environment. Hence, selection can be made on the accessions as ample genetic variation exist that could be utilized in the crop improvement.